Music Education Students’ Ways of Learning and Consumption of Cultures - Laovanich, Vitchatalum; Chuppunnarat, Yootthana (Journal of Urban Culture Research, 2016)
The aims of this research were first to study cultures outside the ASEAN Economic Community – AEC that have entered Thai society and their affects on the original values of music education students during the 10-year period from 2006-15. Secondly, to study the ways of life and learning behaviors of the music education students at the higher education level caused by the consumption of cultures outside the AEC. The qualitative research method in collecting and analyzing data from documents and interviews was utilized. The research focused on a sample group of educators with direct experience in the with music education graduates and those with direct experience in hiring graduates of music education programs. The research results showed that the influence of foreign cultures outside the AEC are composed of two factors: 1) The consumption of music and entertainment content and 2) the use of modern media and technology. These variables affect the ways of life and learning behaviors of the music education students throughout the 10-year period.